Potentialities and Promotion of Tourism in Dailekh District, Nepal - Bishwakarma, Kirpa Ram; Basnet, Yasoda (Journal of Tourism & Adventure, 2018)
This paper argues tourism represents dynamic mobility of persons from place to places to know lifestyle, culture and civility of the particular places of interests. It plays significant roles in transforming lifestyle and comprehension. It is a smokeless industry, which contributes abundance in recessive aspects of culture and economic enhancement. Comprehending one’s culture and access in basic human development infrastructures denote with the influx of tourists and their mobility. Advanced tourism discloses potentialities of inaccessible places and makes strong ties with dimensional social aspects promoting art, culture and architecture. Dailekh fosters valuable natural, architectural, religious and cultural heritages that remain undisclosed to the external societies. Th e methodology of study was focus group discussion and personal communication incorporated to the secondary sources. The creative capacity of people and the pilgrimage tourism can create best income opportunities to the fellow citizens with the rational blend of nature, human skills and social capital. Natural beauty with conglomeration of several caste and ethnicity tempts the visitors so that the rational management of the tourist sites, cultural heritages and the places of interests like Sheersthan, Navisthan, Dhuleshwor, Padukasthan and Kotila could foster pilgrimage tourism and contribute to state development.